2017
DOI: 10.35613/ccl.2017.1072
|View full text |Cite
|
Sign up to set email alerts
|

How bosses can make or break leadership development programs

Abstract: Center for Creative Leadership ® and CCL ® are registered trademarks owned by the Center for Creative Leadership.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…This well-supported leader will be more likely to effectively develop the desired skills than one whose manager does not take the time to inquire about and support her development. In line with this, a study by Young, Champion, Raper & Braddy (2017) showed that participants with greater boss support reported significantly higher improvement in development outcomes including self-awareness, leadership capability, leadership effectiveness and engagement.…”
Section: Context Factorsmentioning
confidence: 61%
“…This well-supported leader will be more likely to effectively develop the desired skills than one whose manager does not take the time to inquire about and support her development. In line with this, a study by Young, Champion, Raper & Braddy (2017) showed that participants with greater boss support reported significantly higher improvement in development outcomes including self-awareness, leadership capability, leadership effectiveness and engagement.…”
Section: Context Factorsmentioning
confidence: 61%
“…Leader capability is the possession of leadership skills, whereas leader effectiveness is putting those skills into action. A series of confirmatory factor analyses provided support for the discriminant validity of these measures (Young et al., 2017). Hypotheses 1a and 1b were as follows: A favorable-feedback environment is positively related to perceptions of improvement in (a) leader effectiveness and (b) leader capability following the 360 LDP.…”
Section: -Degree-feedback Leader-development Programsmentioning
confidence: 93%
“…Perceived improvement in leader effectiveness was measured with three items from Young et al. (2017) using a 10-point Likert-type scale (1 = not at all , 10 = very great extent ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation